CARDIOVASCULAR SAFETY IN THERAPY OF DIABETES MELLITUS TYPE 2 - A. F. VERBOVOY; A. V. PASHENTSEVA; Y. A. DOLGIKH; A. S. OSINA; L. A. SHARONOVA (Медицинский совет, 2016)
Diabe tes mellitus is chronical disease, lead to vascular complications. The safety of hypoglycemic therapy influences on cardiovascular complications. In this review results of some large-scale clinic trials directed to prevention of cardiovascular complications are provided.